Proof that Equality is Symmetric

9. Using our logical axioms and structural rules as discussed in class (but not the axioms of ZFC), give a formal proof that equality is symmetric: i.e., prove ⊢∀x∀y(x=y→y=x) in our formal system.

Statement: For all x and y, if x = y this implies y = x. ⊢∀x∀y(x=y→y=x)

Expression Axiom/Explanation
x = y ⊢ x = y Axion of Assumption
x = y ⊢ x = x =I
(x = y) ⊢ (y = x) =E
⊢ (x = y → y = x) →I
⊢ ∀x ∀y (x = y → y = x) ∀I
Unless otherwise stated, the content of this page is licensed under Creative Commons Attribution-ShareAlike 3.0 License